BiodiversityR packages for Community Ecology and Suitability Analysis - CGIAR Research Program on Forests, Trees and Agroforestry (2021)
Fully developed tool available for use. New packages added. Kindt, Roeland, 2020. BiodiversityR: Package for Community Ecology and Suitability Analysis. Version 2.12-1. URL